IMPORTANCE OF OER INIMPROVING HIGHER EDUCATION. - T Pote, Ramesh (International Journal of Psychosocial Rehabilitation, 2021)
The rapid growth of OER provides new opportunities for teaching and learning; at the same time, they challenges established views about teaching and learning practices in higher education. In Indian economy, from the last two decades, it has achieved much more than what the world has expected. The quality of life has improved both in rural and urban settings. The reason of this high achievement is due to good policies and programs started by government. Another reason being that the common man has access to education, specifically at school level. But the task of converting a huge human resource (16–24 years) into knowledge workers’ rests on the kind and quality of tertiary education being provided to the common man. If we look at the past decade (2001-2011),. As per the latest figure given, almost 19% of total population in the age group of 18-23 is studying in higher education in almost 712 universities, 36,671 colleges and 11,445stand-aloneeducational institutions in management, technical, medical and other professional institutes (Educational Statics at a Glance, MHRD, 2014). With such a huge expansion, what is required is the quantitative and qualitative expansion of resources-infrastructural, educational, technological human and more so economical. government has opened the private sector and thinking on the lines of Foreign Direct Investment (FDI) in education sector. Higher education and research, which will pave new way to the higher education sector. Since equity, access and quality in higher education are the prime concern of the government, therefore government has realized that Information and Communication technology (ICT) sector will play a crucial role in expanding higher education and that’s why it has launched nationwide centrally sponsored mission called National Mission on Education through Information and Communication Technology (NMEICT) and National Knowledge Network (NKN), through which universities as well as colleges of higher education will be connected. National Knowledge Network will connect all the universities, whereas other projects related to education like National Programma on Technology-Enhanced Learning (NPTEL), Eklavya (An open educational portal of Indian Institute of Bombay), National Repository of Open Educational Resource (NROER), etc have been launched to not only connect the higher education institutes but also help the stakeholders access the good-quality educational resources material. This paper examines the innovative and resourceful open education resources and the importance of open education resources in education. Therefore, OER present a range of opportunities to institutions of higher education, teachers and learners of higher education, as well as administrators of higher education